Homeopathy and Diabetes: Current Evidence and Future Prospects - Tarro, Giulio; De Giorgio, Giovanni (British Journal of Healthcare and Medical Research, 2026)
Scientific research into the treatment of diabetes mellitus represents one of the major healthcare challenges and, today, is very broad and in-depth, so much so that it also focuses on potential homeopathic treatments. We examined the scientific literature and realized that, in recent years, highly significant clinical and preclinical studies have been conducted that could reveal new therapeutic opportunities and interesting homeopathic perspectives. Today, the possibility of managing diabetes homeopathically is being carefully evaluated; in fact, thanks to in vitro and in vivo studies, and clinical trials, the scientific literature continues to grow and provide encouraging information: clinical and preclinical evidence, although limited, suggests the role of homeopathy in the treatment of prediabetes, diabetes, diabetic neuropathy, diabetic ulcers, and any comorbidities. It is undeniable that the currently available results need to be consolidated with further scientific evidence, but it is also undeniable that they represent the building blocks of a small but solid foundation of knowledge that can support future responsible, serious, and rigorous research. We therefore believe that further investigation is necessary to fully understand the role homeopathic medicine could play in the field of diabetes, but we also believe that the knowledge currently available is already very interesting and can significantly encourage studies on homeopathic remedies that can be used to treat prediabetes, diabetes, and any comorbidities.